(untitled) (Agroindustria, Sociedad y Ambiente, 2023)
The carrot (Daucus carota L.) belonging to the Apiaceae has two stages of growth. Proper planting spacing allows the crop to develop in excellent conditions, without having problems due to nutrient competition and stress due to the lack of space for its development. This research aims to evaluate the growth and development of carrot plants under two planting densities (DS), and the quality of the roots. The trial was carried out in Cubiro, Lara state. The design used was completely randomized blocks with 5 replicates, 2 seeding densities: T1 (15 cm x 50 cm) and T2 (30 cm x 50 cm). The evaluated variables were emergence percentage (%E), plant height (AP), number of leaves (NH) and root quality (CR), by estimating the percentage of deformed roots (% RD), number of roots with cracks (NRR) length (LR) and diameter (DR) thereof. The %E, the AP a and the NH were similar in the two DS used. In the treatment with the highest DS, the highest percentage of second quality roots and cracked roots was found. The LR and DR in the two DS were similar. The fresh mass of first and second grade roots was higher when they were planted at a lower density, while the weight of cracked and deformed roots was lower. The higher the density, the roots with lower weights are produced and more cracked and deformed roots are obtained, however there is a higher yield.